Effect of Drought Stress on Vegetative Growth and Curvularia oryzae Leaf Spot Disease Severity on Oil Palm (Elaeis guineensis) Seedlings - Priwiratama, Hari; Wijayanti, Eka; Wiyono, Suryo; Toding Tondok, Efi; Hendrastuti Hidayat, Sri; Wening, Sri (Jurnal Penelitian Kelapa Sawit, 2025)
Drought stress is one of the factors that may influence the growth of oil palm seedlings. In long term, drought can potentially increase the susceptibility of oil palm to plant diseases. This study aims to analyze the effect of drought on vegetative growth and the severity of Curvularia leaf spot disease. Drought stress was simulated by limiting water application to three-month-old oil palm seedlings at field capacity (KL), 75% KL, 50% KL, and 25% KL levels. In each treatment, inoculation of Curvularia oryzae was conducted by spraying a spore suspension (1 x 105 conidia/mL) evenly on the leaf surface. The results showed that infected seedlings under severe drought stress (25% KL) had lower height and crown width compared to treatments KL. The severity of Curvularia leaf spot disease in plants experiencing severe water stress (25% KL) was lower than in the standard nursery treatment, KL, and 75% KL. In general, it can be concluded that drought stress has contrasting effects on plant growth variables and the severity of Curvularia leaf spot disease.